2021
DOI: 10.1029/2020gh000368
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of COVID‐19 Infections in Kolkata Metropolitan City: A GIS‐Based Study and Policy Implications

Abstract: The COVID‐19 pandemic has affected daily lives of people around the world. People have already started to live wearing masks, keeping a safe distance from others, and maintaining a high level of hygiene. This paper deals with an in‐depth analysis of riskness associated with COVID‐19 infections in Kolkata Municipal Corporation (KMC) at the subcity (ward) level. Attempts have been made to identify the areas with high or low risk of infections using GIS‐based geostatistical approach. Cosine Similarity Index has b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our results emphasized the existence of spatial heterogeneity in herd immunity. Previous studies also indicated that spatial heterogeneity may influence the implementation of interventions, and control strategies should aim at such heterogeneity (Dowdy et al., 2012; Nath et al., 2021; Shrestha et al., 2016; Yechezkel et al., 2020). Therefore, it is necessary to quantify the degree of spatial heterogeneity, identify the “hotspots” and apply intervention against the disease outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Our results emphasized the existence of spatial heterogeneity in herd immunity. Previous studies also indicated that spatial heterogeneity may influence the implementation of interventions, and control strategies should aim at such heterogeneity (Dowdy et al., 2012; Nath et al., 2021; Shrestha et al., 2016; Yechezkel et al., 2020). Therefore, it is necessary to quantify the degree of spatial heterogeneity, identify the “hotspots” and apply intervention against the disease outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the risk to COVID-19 infection using remote sensing and GIS, geographical analysis-based proximity analysis and census data of Jaipur city and socioeconomic parameters (population, population density, percentage of main workers, and percentages of literates) have been employed to identify the risk to COVID-19 infection. Also in India, with the aim of dealing with an in-depth analysis of riskness associated with COVID-19 infections in Kolkata Municipal Corporation at the subcity level, the areas with high or low risk of infections using GISbased geostatistical approach was identified in this area (54). The study results of (54) has shown that the highest risk areas were located in the eastern and western part of the city, to a great extent overlapped with wards containing larger share of population living in slums and/or below poverty level (54).…”
Section: Assessment Of Impacts Of Socio-economic Factors On the Trans...mentioning
confidence: 99%
“…Also in India, with the aim of dealing with an in-depth analysis of riskness associated with COVID-19 infections in Kolkata Municipal Corporation at the subcity level, the areas with high or low risk of infections using GISbased geostatistical approach was identified in this area (54). The study results of (54) has shown that the highest risk areas were located in the eastern and western part of the city, to a great extent overlapped with wards containing larger share of population living in slums and/or below poverty level (54). Impacts of social and economic factors on the transmission of COVID-19 was also assessed in China (55).…”
Section: Assessment Of Impacts Of Socio-economic Factors On the Trans...mentioning
confidence: 99%
“…The abrupt restriction of anthropogenic activities was implemented in India from March 24, 2020 (Kabiraj & Gavli, 2020 ; Srivastava et al., 2020 ), constraining the normal movement of the population (Gautam & Hens, 2020 ). Like the whole country, interstate and intrastate transportation from Kolkata were suspended till May 3, 2020, which was further extended till June 30, 2020 in areas with large COVID‐19 cases categorized as red zones (Banerji & Mitra, 2021 ; Nath et al., 2021 ). During the lockdown, the Indian railway was operating only freight services to transport necessary goods to various parts of the country.…”
Section: Introductionmentioning
confidence: 99%